2020
DOI: 10.3390/ijms21197398
|View full text |Cite
|
Sign up to set email alerts
|

Key Players and Biomarkers of the Adaptive Immune System in the Pathogenesis of Sarcoidosis

Abstract: Sarcoidosis is a systemic inflammatory disease characterized by development of granulomas in the affected organs. Sarcoidosis is often a diagnosis of exclusion, and traditionally used tests for sarcoidosis demonstrate low sensitivity and specificity. We propose that accuracy of diagnosis can be improved if biomarkers of altered lymphocyte populations and levels of signaling molecules involved in disease pathogenesis are measured for patterns suggestive of sarcoidosis. These distinctive biomarkers can also be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 98 publications
1
46
1
Order By: Relevance
“…The Tregs have also been reported in the mutations of BTNL2 (Butyrophilin like 2) and ANXA11 (Annexin A11), leading to the development of gene products with anti-inflammatory and immune regulatory properties. These lead to the development of an imbalance between regulatory T cells and Th17, responsible for autoimmune diseases 12 . gene expression of Tbx21, finally enhances IFNγ gene transcription competence leading to an increase in the IFN-γ production.…”
Section: Fig 1: Pathogenesis Of Development Of Granuloma In Sarcoidosismentioning
confidence: 99%
See 2 more Smart Citations
“…The Tregs have also been reported in the mutations of BTNL2 (Butyrophilin like 2) and ANXA11 (Annexin A11), leading to the development of gene products with anti-inflammatory and immune regulatory properties. These lead to the development of an imbalance between regulatory T cells and Th17, responsible for autoimmune diseases 12 . gene expression of Tbx21, finally enhances IFNγ gene transcription competence leading to an increase in the IFN-γ production.…”
Section: Fig 1: Pathogenesis Of Development Of Granuloma In Sarcoidosismentioning
confidence: 99%
“…The severity of inflammation can be identified by this scan by the use of a radioactive material Ffluorodeoxyglucose (iv) 12,24 .…”
Section: Pet Scan (Positron Electron Tomography)mentioning
confidence: 99%
See 1 more Smart Citation
“…They are tightly packed cell clusters, forming the primary core of multinucleated giant cells, epithelioid histiocytes, and macrophages enclosed in a lymphocyte collar [12]. Although CD4+ T-cells are majorly localized within the lymphocyte collar, a few B cells, CD8+ Tcells, broblasts, and plasma cells are present, too [13]. CD4+ T lymphocytes are crucial in sarcoidosis progression as they recruit leukocytes, eventually generating granulomas, whose interaction with B cells stimulates the production of antibodies [14].…”
Section: Introductionmentioning
confidence: 99%
“…From these findings, the authors concluded that hTERT is a relevant antigen in HPV-driven SCCA disease and that the levels of M-MDSC influence TH1-adaptive immune responses and patient survival. In researching biomarkers of sarcoidosis, an inflammatory disease of unknown origin, Zhou and Arce provide an important review of the key players and biomarkers of the adaptive immune system in the pathogenesis of this disorder [ 9 ]. The authors highlight that there is no specific biomarker for sarcoidosis and that the majority of biomarkers examined to date remain unvalidated in the clinical setting or are insufficiently specific or sensitive for use in isolation for the purpose of clinical-decision making.…”
mentioning
confidence: 99%